PENGEMBANGAN PINK MIANA MENJADI PRODUK UNGGULAN DAERAH BERBASIS IPTEK UNTUK MEWUJUDKAN KESEJAHTERAAN MASYARAKAT DI DESA PUNTUKREJO - Farhan F. A.; Fortuna R. A; Firman D; Dora A. F.; Dila R.; Ruben H. A.; Niko Dias S. P.; Trisya K. M.; Rysca Indreswari; Fakhrul Fathoni (Bahasa Indonesia, 2022)
Pink Miana plant (Coleus scuttelarioides) is a miana variety that is only cultivated in one of the tourism msmes The Lawu Fresh, Puntukrejo Ngargoyoso Village, Karanganyar, Central Java. This ornamental plant, which is famous for its unique leaf color, turns out to contain various substances such as antioxidants and anti-inflammatories that are good for the body's immunity. However, the abundance of potential possessed by Miana is not balanced with the capabilities of the local community in its processing. Improper processing of Pink Miana can lead to reduced or loss of content of these substances if processed with too hot temperatures. The method used in solving these problems is controlled boiling. Controlled boiling is a method of boiling using low heat with regular temperature monitoring so as not to exceed the maximum temperature that the material can accept. The findings obtained are syrup products made from the first miana leaves "Pink Fresh" which contains high antioxidants and anti-inflammatories that are efficacious for the body's immunity. The purpose of making functional drinks based on miana is to provide an innovative variety of health drinks compared to those already on the market. The creation of functional beverage products based on miana "Pink Fresh" is expected to be a product supporting the body's immune system by implementing learning-based activities to utilize the potential of the village into a product with high economic value in order to achieve the economic empowerment of the village community. Young people are the main target market of the "Pink Fresh" product because of its taste innovation that is unlike other health drinks. Despite using a pre-order system, the first sales of the "Pink Fresh" product received rave reviews from consumers until it reached 70 bottles in the first order. Abstrak Tanaman Pink Miana (Coleus scuttelarioides) merupakan varietas miana yang hanya dibudidayakan di salah satu UMKM pariwisata The Lawu Fresh, Desa Puntukrejo Ngargoyoso, Karanganyar, Jawa Tengah. Tanaman hias yang terkenal dengan keunikan warna daunnya ini ternyata mengandung berbagai zat seperti antioksidan serta antiinflamasi yang baik bagi imunitas tubuh. Akan tetapi, melimpahnya potensi yang dimiliki miana tidak diimbangi dengan kapabilitas masyarakat setempat dalam pengolahannya. Pengolahan Pink Miana yang kurang tepat dapat menyebabkan berkurang atau hilangnya kandungan zat- zat tersebut jika diolah dengan suhu yang terlalu panas. Metode yang digunakan dalam pemecahan permasalahan tersebut adalah controlled boiling. Controlled boiling merupakan metode merebus menggunakan api kecil dengan pengawasan suhu yang teratur agar tidak melampaui suhu maksimal yang dapat diterima bahan. Adapun hasil temuan yang diperoleh adalah produk sirup berbahan dasar daun miana pertama “Pink Fresh” yang mengandung antioksidan serta antiinflamasi tinggi yang berkhasiat bagi imunitas tubuh. Tujuan dari pembuatan minuman fungsional berbahan dasar miana adalah memberikan variasi minuman kesehatan yang inovatif dibandingkan yang telah ada di pasaran. Terciptanya produk minuman fungsional berbahan dasar miana “Pink Fresh” diharapkan dapat menjadi produk penunjang imun tubuh dengan penerapan kegiatan berbasis based learning untuk memanfaatkan potensi desa menjadi produk dengan nilai ekonomis tinggi guna mencapai keberdayaan ekonomi masyarakat desa. Kalangan muda menjadi target pasar utama dari produk “Pink Fresh” karena inovasi rasanya yang tidak seperti minuman kesehatan lainnya. Meskipun menggunakan sistem pre-order, penjualan pertama dari produk “Pink Fresh” mendapat sambutan hangat dari para konsumen hingga mencapai 70 botol dalam pesanan pertama.